Morphosyntax-prosody mismatches in Karachay-Balkar An analysis of narrow focus constructions - (:unkn) unknown (John Benjamins Publishing Company, 2020)
This study aims to account for prosodic phrasing and morphosyntax-prosody mismatches in Karachay-Balkar narrow focus constructions. Firstly, based on the analyses of the pitch tracks of utterances we demonstrate how narrow focus shapes prosodic structure and yields mismatches with morphosyntactic structure. Then, in line with Truckenbrodt (1995), we suggest that the driving force for the so-called mismatches is the requirement for focus to be the most prominent constituent in its domain. We propose a top-down model according to which the focus aligns with the right edge of the intonational phrase and inserts a phonological phrase boundary to its left. The proposed focus driven prosodic phrasing can also account for prosodic structuring in polar questions with the question suffix. © 2020 John Benjamins Publishing Company
Keywords: Focus; Karachay-Balkar; Morphosyntax; Polar questions; Prosody; Question suffix